2021
DOI: 10.1007/s10886-021-01294-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drosophila suzukii on Blueberry VOCs: Chemical Cues for a Pupal Parasitoid, Trichopria anastrephae

Abstract: Biocontrol agents such as parasitic wasps use long-range volatiles and host-associated cues from lower trophic levels to nd their hosts. Although, this chemical landscape may be altered by the invasion of exotic insect species. The spotted-wing drosophila (SWD), Drosophila suzukii (Diptera: Drosophilidae), is a highly polyphagous fruit pest native to eastern Asia and recently arrived in South America. The aim of our study was to characterize the effect of SWD attack on the volatile organic compounds (VOCs) of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…There was only host switching to D. suzukii when the host ratio was 80-90% D. suzukii over D. melanogaster. These findings are supported by differences in the evolutionary history between T. anastrephae and both hosts because it is a Neotropical-native parasitoid species [66] coevolved in sympatry with saprophytic drosophilid species, such as those of the D. melanogaster group [26]. This may account for the close trophic association between T. anastrephae and non-pest saprophytic drosophilids, whereas a new trophic association was recently established with D. suzukii.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…There was only host switching to D. suzukii when the host ratio was 80-90% D. suzukii over D. melanogaster. These findings are supported by differences in the evolutionary history between T. anastrephae and both hosts because it is a Neotropical-native parasitoid species [66] coevolved in sympatry with saprophytic drosophilid species, such as those of the D. melanogaster group [26]. This may account for the close trophic association between T. anastrephae and non-pest saprophytic drosophilids, whereas a new trophic association was recently established with D. suzukii.…”
Section: Discussionmentioning
confidence: 81%
“…Thus, T. anastrephae can parasitize D. suzukii puparia in less competitive microhabitats, such as the ground beneath fallen feral peaches and guavas in non-crop areas [35]. Previous studies have shown that most D. suzukii larvae pupate on the ground beneath fallen fruit [57][58][59][60][61][62][63][64][65][66][67][68], and puparia can be attacked by pupal parasitoids [56,69]. These earlier published data, plus information from the current study, reveal that T. anastrephae may exert mortality over D. suzukii puparia isolated on the ground.…”
Section: Discussionmentioning
confidence: 99%
“…They also serve as a deterrent and cause behavioral changes in pests (Dicke & Baldwin, 2010;Gebreyesus Gebreziher, 2020;War et al, 2011). Recently, a study showed that the VOCs emitted by a blueberry infected with SWD were more attractive for a parasitoid than when the blueberry was not attacked (de la Vega et al, 2021).…”
Section: Recruit Beneficials Insects: Associated Swd Natural Enemies ...mentioning
confidence: 99%
“…SWD parasitoids need to find SWD-infested fruit and presumably exploit fruit volatiles as cues, a tritrophic interaction that is not well understood and may be key for successful biological control. The study of these interactions have included the behavioural assessment of wasps in olfactometer tests in response to natural volatile blends from infested fruit (Biondi et al, 2021;de la Vega et al, 2021;Wolf et al, 2020). Because these are complex and dynamic volatile blends, separating its components and evaluating their ecological significance may be useful to further characterize these interactions.…”
Section: Introductionmentioning
confidence: 99%